PIR-B expressing CD8+ T cells exhibit features of Tc1 and Tc17 in SKG mice. (29th June 2019) - Rothe, Kathrin; Quandt, Dagmar; Köhler, Gabriele; Jasinski-Bergner, Simon; Seliger, Barbara; Pierer, Matthias; Wagner, Ulf
Abstract: Objective: In autoimmune arthritis, TCR signalling is attenuated by peripheral tolerance mechanisms. We have described previously a population of inhibitory receptor LIR-1 expressing autoreactive CD8 + T cells in rheumatoid arthritis. Here, we investigated the role of CD8 + T cells in murine autoimmune arthritis by analysing their expression of the mouse orthologue of LIR-1, PIR-B. Methods: Frequencies of PIR-B + CD8 + T cells were determined in the SKG arthritis model. The phenotype of those cells was determined ex vivo by FACS and functionality was investigated by means of cytokine production and cytolytic potential upon activation in vitro . Results: SKG mice, under non-SPF (specific pathogen-free) conditions with clinical symptoms of arthritis, were found to harbour significantly increased frequencies of PIR-B + CD8 + T cells. Those cells showed a pro-inflammatory phenotype with preferential production of IL-17 and IFN-γ. The frequency of those cells correlated inversely with the arthritis score, indicating that they might represent autoreactive, but functionally inhibited, CD8 + T cells. Conclusion: PIR-B + CD8 + T cells from SKG mice show a cytotoxic and pro-inflammatory phenotype. Inhibition of CD8 + T cell autoreactivity by PIR-B/LIR-1 receptor signalling might be a counter-regulatory mechanism to curb autoreactivity and arthritis.